Knowledge of US Midwifery Credentials Among Members of the American College of Nurse‐Midwives. (10th October 2019) - Jefferson, Karen; MacKenzie, Rachel K.; Hackley, Barbara; Perlman, Dana
Abstract : Introduction: Three midwifery credentials are granted in the United States: certified nurse‐midwife (CNM), certified midwife (CM), and certified professional midwife (CPM). Confusion about US midwifery credentials may restrict growth of the midwifery profession. This survey assessed American College of Nurse‐Midwives (ACNM) members' knowledge of US midwifery credentials. Methods: ACNM members (N = 7551) were surveyed via email in 2017. The survey asked respondents to report demographic information and to identify correct statements about the education, certification, and scope of practice of CNMs, CMs, and CPMs. Responses to 17 items about all midwives certified in the United States, a 5‐item subset specific to CNMs/CMs, and one item related to location of midwifery practice by credential were analyzed. Results: Nearly a quarter of the membership (22.1%) responded to the survey. Higher scores on the survey indicated greater identification of correct statements about the education, certification, scope, and location of practice of CNMs, CMs, and CPMs. Significant differences in scores were found among ACNM members based on their level of education, degree of professional involvement in midwifery, and prior practice as a nurse. ACNM members with higher scores on the survey held a doctorate, worked in Region I, and had greater professional leadership involvement in midwifery organizations. Participants with less nursing experience prior to their midwifery education also scored significantly higher on the survey. Discussion: Although two‐thirds of respondents correctly answered items on the preparation, credentialing, and scope of practice of CNMs, CMs, and CPMs, a significant minority had gaps in knowledge. Results of this survey suggest the need for outreach about US midwifery credentials. Future research to replicate and expand upon this survey may benefit the profession of midwifery in the United States.